Research handbook on the ombudsman - Hertogh, Marc, 1968-; Kirkham, Richard; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
The public sector ombudsman has become one of the most important administrative justice institutions in many countries around the world. This international and interdisciplinary Research Handbook brings together leading scholars and practitioners to discuss the state-of-the-art research on this increasingly prominent institution. Traditionally, research on the ombudsman has been conducted from a purely prescriptive or (legal) descriptive perspective, mainly focusing on the ombudsman 'in the books'. By contrast, this book illustrates how empirical research may contribute to a better understanding of the ombudsman 'in action'. It uses new empirical studies and competing theoretical explanations to critically examine important aspects of the ombudsman's work. The Research Handbook is organized in to four parts: fundamentals of the ombudsman; the evolution of the ombudsman; evaluation of the ombudsman; and the ombudsman office and profession. Featuring case studies from Europe, Canada, Asia, Africa, Latin America and Australia, chapters provide a comprehensive global perspective on the issues at hand. This unique Research Handbook will be of great value to researchers in the fields of public law, socio-legal studies and alternative dispute resolution who have an interest in the ombudsman. It will also be a valuable resource for policymakers and practitioners, particularly those working within ombudsman offices.
Foreword / Peter Tyndall -- 1. The ombudsman and administrative justice: from promise to performance / Marc Hertogh and Richard Kirkham -- Part I: Fundamentals of the ombudsman -- 2. The history and evolution of the ombudsman model / Sabine Carl -- 3. Ombudsmen and public authorities: a modest proposal / Nick O'Brien -- 4. The private sector ombudsman / Christopher Hodges -- Part II: The evolution of the ombudsman -- 5. Ombudsmen: 'hunting lions' or 'swatting flies' / Carol Harlow -- 6. The politics of the ombudsman: the Hong Kong experience / Johannes Chan and Vivianne Wong -- 7. The ombudsman and the rule of law / Benny Tai -- 8. The European Ombudsman and the Court of Justice of the European Union: competition or symbiosis in promoting transparency? / Milan Remac -- 9. The rule of law in the European Union: standards of the ombudsman, judge, and auditor / Alex Brenninkmeijer and Emma van Gelder ---10. Ombudspersons in developing countries: the case of Indonesia / Adriaan Bedner -- 11. The transposition of the ombudsman model to the human rights domain: its role as a policy entrepreneur / Carlos Alza Barco -- 12. Fifty years of the ombudsman in Africa / Victor Ayeni -- 13. Ombuds institutions: strengthening gender equality, women's access to justice and protection and promotion of women's rights / Linda C. Reif -- Part III: Evaluation of the ombudsman -- 14. The profile of complainants: how to overcome the 'Matthew effect'? / Bernard Hubeau -- 15. How do complainants experience the ombuds procedure? detecting cultural patterns of disputing behavior: a comparative analysis of users that complain about financial services / Naomi Creutzfeldt and Ben Bradford -- 16. What do government agencies learn from the ombudsman? / Chris Gill -- 17. Ombudsmen in prisons: reviewing and reforming / Matthew Groves -- 18. The national ombudsman and proper police conduct / Yvonne van der Vlugt ---19. The use of own-initiative powers by the ombudsman / Laura Díez Bueso -- 20. Effectiveness and independence of the ombudsman's own motion investigations: a practitioner's perspective from the Netherlands / Maaike de Langen, Emily Govers and Reinier Van Zutphen -- Part IV: Ombudsman office and profession -- 21. Administering access to the public ombuds institution: A case study on the Austrian ombudsman board / Julia Dahlvik and Axel Pohn-Weidinger -- 22. Ombuds can, ombuds can't, ombuds should, ombuds shan't: a call to improve evaluation of the ombudsman institution / Anita Stumckhe -- 23. The Ombudsman in Australia: flourishing, expanding, diversifying, innovating / John McMillan -- 24. Ombudsman values: a guide to practice / Robert Behrens -- 25. The 21st century ombudsperson: a guarantor of democracy / Manuel Lezertua -- 26. What's in a name: a discussion paper on ombud terminology / Varda Bondy and Margaret Doyle -- Part V: Conclusion ---27. An agenda for future ombudsman research: towards a general "ombuds-science" / Marc Hertogh and Richard Kirkham -- Index.
Obsahuje bibliografie, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: veřejný ochránce práv; ombudsman; e-knihy online; e-books online